Como salvar a educação (e o sujeito) pela literatura: sobre Philippe Meirieu e Jorge Larrosa - Flávio Henrique Albert Brayner (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
An increasing number of students are now attempting to bring literature and education closer together. This seems to indicate the emergence of a new pedagogical logos, which attemptsper haps to overcome the frontiers ofreflection imposed by the so-called sciences of education. Some of the approaches, however, not only display visible and understandable limitations,such as the absence of a receptiontheory of fictional texts, but alsodemonstrate the ambition ofrevolutionising pedagogic discoursethrough literature by transforming it intoan aesthetics of existence project. TakingPhilippe Meirieu and Jorge Larrosa asillustrations of the limitations andrevolutionary ambition respectivelythis paper seeks to show howRomanticism and Nietzscheism attemptto build a new discourse, which aspiresto save us, yet again, from the evils ofthe managed society.